Characterization of Immune-Related circRNAs and mRNAs in Human Chronic Atrophic Gastritis - Chao Y; Jin X; Guo R; Zhang H; Cui X; Qi Y (Dove Medical Press, 2024)
Yang Chao,1 Xiya Jin,1 Rui Guo,2 Hongyu Zhang,2 Xueling Cui,3 Yan Qi2 1Department of Gastroendoscopy, China-Japan Union Hospital of Jilin University, Changchun, Jilin, People's Republic of China; 2Department of Immunology, College of Basic Medical Sciences, Jilin University, Changchun, People's Republic of China; 3Department of Genetics, College of Basic Medical Sciences, Jilin University, Changchun, People's Republic of ChinaCorrespondence: Yan Qi; Xueling Cui, Email qiyan@jlu.edu.cn; cxl@jlu.edu.cnBackground: Chronic atrophic gastritis (CAG) is a severe condition characterized by inflammation and loss of appropriate mucosal glands in the stomach. The underlying mechanisms of CAG development remain unclear. Exploring immune-related circular RNAs (circRNAs) could provide insights for potential diagnostic and therapeutic strategies.Methods: Samples from 40 patients with CAG and non-CAG (CNAG) underwent high-throughput sequencing, and EdgeR analysis identified differentially expressed circRNAs and mRNAs. Gene Ontology (GO) analysis elucidated biological functions, while Immune Cell Abundance Identifier (ImmuCellAI) estimated immune cell abundance. Flow cytometry analyzed immune cell infiltration. Weighted gene co-expression network analysis (WGCNA) identified hub genes related to the immune response in CAG. CircRNA-mRNA networks were constructed, and qRT-PCR validated findings.Results: A total of 163 differentially expressed immune-related genes (DEIRGs) were identified between CAG and CNAG. The upregulated immune-related mRNAs in CAG were significantly enriched in antimicrobial humoral response, viral entry into host cells, neutrophil activation, and leukocyte migration. Conversely, downregulated immune-related mRNAs were linked to regulation of natural killer cell-mediated cytotoxicity, positive regulation of adaptive immune response, antigen receptor-mediated signaling pathway, and B cell activation. Immune Cell Abundance Identifier (ImmuCellAI) and flow cytometry confirmed increased neutrophil infiltration in CAG compared to CNAG. WGCNA identified 56 hub immune-related genes. Additionally, circRNA expression profiles in CNAG and CAG were explored, with 19 upregulated and 23 downregulated circRNAs identified in CAG. The upregulated circRNAs were associated with biological processes like carnitine metabolic process and regulation of B cell receptor signaling pathway. A circRNA-mRNA co-expression network was constructed based on five circRNAs highly related to hub immune-related genes. Furthermore, the expression of eight immune-related mRNAs and five circRNAs were validated in CAG.Conclusion: This study is the first systematic analysis of circRNA profiles in CAG and provide important insights for potential immunotherapeutic strategies and early diagnostic biomarkers in CAG treatment.Keywords: chronic atrophic gastritis, circRNAs, immune-related genes, immune cell infiltration